Effects of metazachlor and its major metabolite metazachlor OA on early life stages of marbled crayfish - Velisek, Josef; Stara, Alzbeta; Kubec, Jan; Zuskova, Eliska; Buric, Milos; Kouba, Antonin (Scientific reports, 2020)
The effects of the herbicide metazachlor and its major metabolite metazachlor OA at two concentrations, including environmentally relevant concentrations of metazachlor (0.0115 µmol/l and 0.0790 µmol/l) and metazachlor OA (0.0117 µmol/l and 0.0805 µmol/l), respectively, were evaluated on early ontogeny, growth, behaviour, oxidative stress, antioxidant enzyme levels, histology, and mortality of marbled crayfish Procambarus virginalis. Both tested concentrations of metazachlor and metazachlor OA were associated with significantly lower growth and delayed ontogenetic development compared to controls. Exposure of metazachlor at 0.0115 µmol/l and metazachlor OA at 0.0117 µmol/l and 0.0805 µmol/l resulted in significantly lower activity of total superoxide dismutase (SOD), catalase (CAT), glutathione s-transferase (GST), glutathione reductase (GR), and reduced glutathione (GSH) compared with control and resulted in gill anomalies ranging from wall thinning to focal disintegration of branchial structure. Metazachlor at the environmentally relevant concentration of 0.0790 µmol/l was associated with significant alterations of crayfish distance moved and walking speed. The potential risk associated with metazachlor use in agriculture related to effects on non-target aquatic organisms.
Keywords: chemické látky znečišťující vodu; Embryo, Nonmammalian; oxidační stres; antioxidancia; Glutathione Reductase; ekotoxikologie; Hepatopancreas; Water Pollutants, Chemical; Herbicides; lokomoce; hepatopankreas; glutathion; Animals; Locomotion; ženské pohlaví; Antioxidants; zvířata; Acetamides; glutathionreduktasa; herbicidy; severní raci; Glutathione; Ecotoxicology; Gills; Superoxide Dismutase; acetamidy; Female; Oxidative Stress; žábry; superoxiddismutasa; embryo nesavčí; Astacoidea